2018
DOI: 10.29298/rmcf.v9i50.239
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la intemperización y proceso en las características físicas, mecánicas y energéticas de briquetas

Abstract: Las industrias forestales generan residuos de aserrín que son subutilizados, frecuentemente estos se acumulan durante años, lo que puede propiciar incendios y contaminación. Los objetivos de la presente investigación fueron comparar las propiedades energéticas entre el aserrín fresco e intemperizado de la madera de Pinus pseudostrobus, y determinar algunas propiedades físicas y mecánicas de briquetas elaboradas a partir de ellos. El aserrín se caracterizó según su distribución granulométrica, contenido de hume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…These results are generally close to the values previously reported for these sawdust samples , and are located within the reported range (0.5% to 37.9%) for biomass (Vassilev et al 2010). Carrillo-Parra et al (2018) report values of 10.9% to 14.1% in fresh pine sawdust briquettes and values of 11.0% to 12.6% in briquettes made with weathered pine sawdust. The calorific value of the briquettes varied from 20.5 MJ/kg (Sample 2) to 22.8 MJ/kg (Sample 12) with statistically significant differences (p = 0.0000) (Table 2, Fig.…”
Section: Fig 7 Graphs Of Means For Volatile Matter Of Briquettessupporting
confidence: 91%
See 4 more Smart Citations
“…These results are generally close to the values previously reported for these sawdust samples , and are located within the reported range (0.5% to 37.9%) for biomass (Vassilev et al 2010). Carrillo-Parra et al (2018) report values of 10.9% to 14.1% in fresh pine sawdust briquettes and values of 11.0% to 12.6% in briquettes made with weathered pine sawdust. The calorific value of the briquettes varied from 20.5 MJ/kg (Sample 2) to 22.8 MJ/kg (Sample 12) with statistically significant differences (p = 0.0000) (Table 2, Fig.…”
Section: Fig 7 Graphs Of Means For Volatile Matter Of Briquettessupporting
confidence: 91%
“…Values reported for fresh pine sawdust briquettes range from 78.5% to 79.8%, while when using weathered pine sawdust, the values found varied from 77.8% to 81.0% (Carrillo-Parra et al 2018), these values are close to the lowest result found here. The range reported for biomass goes from 47.8% to 86.3% (Vassilev et al 2010).…”
Section: Fig 7 Graphs Of Means For Volatile Matter Of Briquettessupporting
confidence: 84%
See 3 more Smart Citations